SYNTHESIS OF PROPYLENE CARBONATE FROM UREA AND 1,2-PROPYLENE GLYCOL OVER METAL CARBONATES - Yali Guo; Birong Zhang; Dongfang Wu; Jiancheng Zhou (Chemical Industry and Chemical Engineering Quarterly, 2011)
A series of single-metal carbonates and Pb-Zn mixed-metal carbonates were prepared as catalysts for alcoholysis of urea with 1,2-propylene glycol (PG) for the synthesis of propylene carbonate (PC). The mixed carbonates all show much better catalytic activities than the single carbonates, arising from a strong synergistic effect between the two crystalline phases, hydrozincite and lead carbonate. The mixed carbonate with Pb/Zn = 1:2 gives the highest yield of PC, followed by the mixed carbonate with Pb/Zn = 1:3. Furthermore, Taguchi method was used to optimize the synthetic process for improving the yield of PC. It is shown that the reaction temperature is the most significant factor affecting the yield of PC, followed by the reaction time, and that the optimal reaction conditions are the reaction time 5 h, the reaction temperature 180 °C and the catalyst amount 1.8 mass%, resulting in the highest PC yield of 96.3%.